Analysis of Communication System for Community Empowerment Based on Integrated Plant Management Implementation Movement Program (GPPTT) - Selly Oktarina; Norhazlina Fairuz Musa Kutty; Eko Purwanto; Mirza Shahreza; Abdul Basit (Jurnal Mamangan, 2023)
Empowerment communication is important so the people become empowered through effective communication. The effectiveness of communication is inseparable from the role of the institutions involved in program implementation. This study aims to analyze the communication system in empowering the community the “jajar legowo” cropping system in the Integrated Plant Management Implementation Movement (GPPTT) program. The theory used in this study is the adoption of innovation. The research method is qualitative in nature, namely based on the results of field observations supported by literature studies of related journals. Data were analyzed descriptively by providing understanding and explanation so that it was easy to understand. The focus of the study was carried out in Ogan Ilir Regency, South Sumatra, as one of the implementers of the GPPTT and as a Food Barn. The communication system based on black box analysis shows that community empowerment based on the GPPTT Program is good, it is carried out based on five elements consisting of environmental input, controlled input, uncontrolled input, desired input and unwanted input. The pattern of analysis of the GPPTT program system is based on the existence of GPPPT policies, empowerment strategies and technical guidelines that affect the empowerment of farmers in adopting the jajar legowo cropping system so as to produce a paradigm shift in empowerment communication. A community empowerment communication system based on the GPPTT program based on black box analysis is a problem solving solution for farmers to adopt technology to be independent.